Comparative Transcriptome Analysis Reveals the Mechanisms Underlying Differences in Salt Tolerance Between indica and japonica Rice at Seedling Stage - Kong, Weilong; Sun, Tong; Zhang, Chenhao; Deng, Xiaoxiao; Li, Yangsheng (Frontiers in Plant Science, 2021)
Screening and breeding more salt-tolerant varieties is an effective way to deal with the global reduction in rice (Oryza sativa L.) yield caused by salt stress. We herein performed a comparative transcriptomic analysis under salt stress in contrasting two rice genotypes, namely RPY geng (japonica, tolerant variety) and Luohui 9 (named as Chao 2R in this study, indica, susceptible variety). 7208 and 3874 differentially expressed genes (DEGs) were identified under salt stress in Chao 2R and RPY geng, separately. Of them, 2714 DEGs were co-expressed in both genotypes, while 4494 and 1190 DEGs were specifically up/down-regulated in Chao 2R and RPY geng, respectively. Gene ontology (GO) analysis results provided a more reasonable explanation for the salt tolerance difference between the two genotypes. Furthermore, we highlighted the important pathway and essential transcription factors related to salt tolerance in RPY geng specific DEGs sets based on Mapman annotation and TF identification. On the other hand, through Meta-QTLs mapping and homologous analysis, we screened out 18 salt stress-related candidate genes (RPY geng specific DEGs) in 15 Meta-QTLs. Our findings not only offer new insights into the difference in salt stress tolerance between the rice subspecies but also provide critical target genes to facilitate gene editing to enhance salt stress tolerance in rice.